2020
DOI: 10.1111/ijac.13463
|View full text |Cite
|
Sign up to set email alerts
|

Permeability behavior of silicon carbide‐based membrane and performance study for oily wastewater treatment

Abstract: Porous SiC ceramic is considered as a suitable material for hot gas filtration, microfiltration, and many others industrial applications. However, full utilizations of porous SiC ceramics have been limited by high‐processing costs. In this study, mullite‐bonded porous SiC ceramics membranes were prepared using commercial SiC powder, alumina, clay, and different sacrificial pore formers. The effect of different pore formers on the microstructure, mechanical strength, porosity and pore size distribution, air, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 46 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Table VIII lists the chemical compositions of various inorganic industrial wastes used as alternative raw materials in the production of porous ceramics. Among them, those from the brewing [33,34], ornamental rocks [35][36][37], ceramic [35,[38][39][40][41][42], metallurgical [43,44] and mining [45][46][47][48][49] industries, thermal power plants [96][97][98] and others [13,50,51,99] stand out. It is observed that the vast majority of these wastes are mainly composed of SiO 2 , that is, they can be used satisfactorily as sources of silica in ceramic technology.…”
Section: Inorganic Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Table VIII lists the chemical compositions of various inorganic industrial wastes used as alternative raw materials in the production of porous ceramics. Among them, those from the brewing [33,34], ornamental rocks [35][36][37], ceramic [35,[38][39][40][41][42], metallurgical [43,44] and mining [45][46][47][48][49] industries, thermal power plants [96][97][98] and others [13,50,51,99] stand out. It is observed that the vast majority of these wastes are mainly composed of SiO 2 , that is, they can be used satisfactorily as sources of silica in ceramic technology.…”
Section: Inorganic Wastementioning
confidence: 99%
“…Coal ash from power plants: coal ash is generated in large quantities as a by-product of thermal power plants [96], and is considered to be highly hazardous to the environment due to its persistently toxic trace elements [98]. In this sense, environmentally friendly use of this type of waste is an important issue for the prevention of environmental pollution [96]. The main chemical components of coal fly ash (silica, alumina) are similar to those of clays and kaolin, which are used as starting materials to fabricate porous ceramics [98].…”
Section: Inorganic Wastementioning
confidence: 99%
“…Silicon carbide (SiC) is an intriguing material owing to its remarkable properties and versatility, which make it suitable for numerous industrial applications. [1][2][3][4][5][6][7][8] Porous SiC ceramics with excellent mechanical properties, [9][10][11][12][13][14] high chemical stability, [15][16][17][18][19] good permeability, [20][21][22][23][24] and controllable thermal [25][26][27] and electrical properties [28][29][30] have gained immense attention for both structural and functional applications. Although the practical use of SiC has mostly been limited to structural applications, it has been extensively investigated recently [25][26][27][28][29][30][31][32][33][34][35] for advanced functional applications owing to its semiconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, silicon carbide (SiC) ceramics have been extensively utilized in various industries, including aerospace, aeronautics, automotive, biomedical, nuclear reactors, filtration, heat exchangers, concentrated solar power, thermoelectric conversion, catalytic support, membranes, thermal insulators, gas turbines, semiconductor processing parts, and diesel particulate filters, owing to their excellent high‐temperature stability, low bulk density, high thermal conductivity, excellent high‐temperature strength, high oxidation and corrosion resistances at high temperatures, and excellent chemical stability 1–38 …”
Section: Introductionmentioning
confidence: 99%